Facile synthesis of copper ions chelated sand via dopamine chemistry for recyclable and sustainable catalysis. (10th August 2019) - Wang, Ning; Zhang, Zhongren; Huang, Juanru; Hu, Yunxia
Graphical abstract: Highlights: Cu ions chelated sand (Cu-PDA@Sand) was simply synthesized through dopamine chemistry. Low-cost Cu-PDA@Sand exhibited efficient catalytic reduction properties towards organic dyes in the presence of NaBH4 . Cu-PDA@Sand could be recovered by self-sedimentation and reused for 20 cycles. Cu-PDA@Sand presented long-term high catalytic activities. Abstract: Metal-based catalysts present highly efficient catalytic activities towards organic dyes and their intermediates for color removal. However, several issues are needed to be addressed urgently for their large-scale practical applications, such as the cost, stability and recyclable use of these catalysts. In this work, we developed a facile approach to chelate Cu ions on the polydopamine-coated sand (Cu-PDA@Sand) and investigated their catalytic properties towards the decoloration of organic dyes or intermediate including 4-nitrophenol (4-NP), methylene blue (MB), and congo red (CR). Our results found that the copper ions from Cu-PDA@Sand were the mixture of Cu (I) and Cu (II), and the molar fraction of Cu (I) over Cu (II) was increased from the original 3:2 to 4:1 in the presence of NaBH4 . The reduction of these organic dyes or intermediate followed the first order kinetics, and the apparent reduction rate kapp of CR was larger than that of MB and 4-NP under similar conditions. Additionally, the optimized kapp of 4-NP could reach to 1.28 min −1, which is much higher than the reported results from literature. The recyclability test of Cu-PDA@Sand showed that the reduction efficiency of Cu-PDA@Sand maintained 100% during the successive 20 cycles. Additionally, Cu-PDA@Sand was demonstrated to present long-term stability and catalytic activities after soaking Cu-PDA@Sand in water for 30 days. Our research demonstrated that the easy-prepared low-cost Cu-PDA@Sand catalyst would have a great potential in the practical applications for color removal of the dye-containing wastewater.